Neurological soft signs as a marker of cognitive impairment severity in people living with HIV. (August 2018) - Toro, Pablo; Ceballos, María Elena; Pesenti, José; Inostroza, María; Valenzuela, Daniela; Henríquez, Fernando; Forno, Gonzalo; Herold, Christina; Schröder, Johannes; Calderón, Jorge
Highlights: We propose neurological soft signs examination as a screening tool in HIV patients. Neurological soft signs are a clinical marker of HIV- associated Neurocognitive Disorder. Neurological soft signs are related to the severity of the cognitive disorder. Abstract: HIV-associated neurocognitive disorders (HAND) include asymptomatic neurocognitive impairment (ANI), mild neurocognitive disorder (MND) and HIV-associated dementia. Early recognition of HAND is crucial, and usually requires thorough neuropsychological testing. Neurological soft signs (NSS), i.e. minor motor and sensory changes, a common feature in severe psychiatric disorders, may facilitate early diagnosis. NSS were examined using the Heidelberg NSS Scale in 18 patients with ANI, 21 with MND, 28 HIV positive patients without HAND, and 39 healthy controls matched for age, gender, and education. The highest NSS scores were obtained in the MND patients (13.3 ± 10.0, p < 0.0001) followed by those with ANI (11.7 ± 10.6), the HIV positive subjects without neurocognitive deficits (8.0 ± 4.1) and the healthy controls (3.8 ± 3.2). This result was confirmed when age and years of school education were entered as covariates. No significant correlations between NSS and CD4 counts or any other clinical variables were found among the HIV positive groups. Our results demonstrate that NSS are frequently found in both ANI and MND but not HIV positive patients without neurocognitive deficits. NSS may facilitate the screening of HIV positive patients for ANI and MND as an easier and less expensive clinical tool.